First measurement of the CP-violating phase [phi] dd [bar] s in B0s→(K+π−)(K−π+) decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Grünberg, Oliver; Han, Xiaoxue; et al. (Journal of high energy physics, 2018)
A flavour-tagged decay-time-dependent amplitude analysis of B s 0 → (K+π−)(K−π+) decays is presented in the K±π∓ mass range from 750 to 1600MeV/c2. The analysis uses pp collision data collected with the LHCb detector at centre-of-mass energies of 7 and 8 TeV, corresponding to an integrated luminosity of 3.0 fb−1. Several quasi-two-body decay modes are considered, corresponding to K±π∓ combinations with spin 0, 1 and 2, which are dominated by the K 0 * (800)0 and K 0 * (1430)0, the K*(892)0 and the K 2 * (1430)0 resonances, respectively. The longitudinal polarisation fraction for the B0s→K∗(892)∘K¯¯¯¯¯∗(892)0Bs0→K∗(892)∘K¯∗(892)0 B_s^0→ K^{* }(892){}^{°}{\overline{K}}^{* }{(892)}^0 decay is measured as fL = 0.208 ± 0.032 ± 0.046, where the first uncertainty is statistical and the second is systematic. The first measurement of the mixing-induced CP-violating phase, ϕdd¯¯¯sϕsdd¯ φ_s^{d\overline{d}} , in b→dd¯¯¯sb→dd¯s b→ d\overline{d}s transitions is performed, yielding a value of ϕdd¯¯¯s=−0.10±0.13(stat)±0.14ϕsdd¯=−0.10±0.13(stat)±0.14 φ_s^{d\overline{d}}=-0.10± 0.13\left(stat\right)± 0.14 (syst) rad. Open image in new window
The LHCb collaboration: R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, N. Skidmore, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]
Im Titel sind "+" und "-" hochgestellt
Im Titel sind "0" und "s" untereinander geschrieben: "0" hochgestellt, "s" tiefgestellt
Im Titel sind "dd̄" und "s" untereinander geschrieben: "dd̄" hochgestellt, "s" tiefgestellt
Im Titel werden "phi" "pi" als griechische Buchstaben dargestellt